Americanon : an unexpected U.S. history in thirteen bestselling books - McHugh, Jess (New York Dutton, 2021)
"What does it take to be a good American? And who gets to decide? Journalist Jess McHugh examines thirteen seemingly innocuous, mega-bestselling reference books, guidebooks, and self-help books that have become blueprints for core American values and shaped our national story"--
The old farmer's almanac -- Webster's speller and dictionary (1783/1828) -- Benjamin Franklin's autobiography -- The McGuffey readers (1836) -- A handbook to American womanhood -- Etiquette in society, in business, in politics and at home -- How to win friends and influence people (1936) -- The Betty Crocker cookbook (1950) -- Everything you always wanted to know about sex* (*but were afraid to ask) (1969) -- Surviving the 80s -- Epilogue.
Includes bibliographical references and index.
HB
Keywords: National characteristics, American; Books and reading -- United States -- History; Social values -- United States -- Miscellanea; United States -- Social life and customs -- Miscellanea